Kanwal athween jamaat ke liye - Farooqui, Fouzia Ahsan (Karachi: Oxford university press, 2023)
Kanwal for Class 8 is an Urdu textbook by Oxford University Press that enhances advanced language skills through diverse literary texts, including stories, poems, and essays. It focuses on reading comprehension, creative expression, and grammar, fostering critical thinking and an appreciation for Urdu literature and culture. The book aims to strengthen students' linguistic and analytical abilities.
Keywords: Urdu